Elevated plasma TFPI activity causes attenuated TF-dependent thrombin generation in early onset preeclampsia - Egan, Karl; O’Connor, Hugh; Kevane, Barry; Malone, Fergal; Lennon, Aine; Zadjali, Amani Al; Cooley, Sharon; Monteith, Cathy; Maguire, Patricia; Szklanna, Paulina B.; Allen, Seamus; McCallion, Naomi; Áinle, Fionnuala Ní (Thrombosis and Haemostasis, 2017)
Early onset preeclampsia (EOP) is a pregnancy-specific proinflammatory disorder that is characterised by competing thrombotic and bleeding risks. It was the aim of this study to characterise thrombin generation, a major determinant of thrombotic and bleeding risk, in order to better understand the haemostatic balance in patients with EOP. Patients with EOP were recruited at the Rotunda Hospital, Dublin. Twenty-six cases of EOP were recruited over a 21-month period, out of 15,299 deliveries at the Rotunda. Blood samples were collected into sodium citrate plus corn trypsin inhibitor anticoagulated vacutainers, platelet-poor plasma was prepared, and calibrated automated thrombography was used to assess thrombin generation. Results were compared to age and sex-matched non-pregnant controls (n=13) and age-and gestation-matched pregnant controls (n=20). The rate and extent of thrombin generation triggered by low-dose tissue factor (TF) was significantly reduced in patients with EOP compared to pregnant controls, most significantly in cases of severe EOP. EOP patients displayed a trend towards an increased response to endogenous activated protein C and thrombomodulin relative to pregnant controls. Plasma tissue factor pathway inhibitor (TFPI) activity was increased in EOP patients. Inhibition of TFPI abolished the attenuation of thrombin generation stimulated by low-dose TF. In conclusion, patients with EOP are characterised by an attenuated coagulation response characterised by reduced thrombin generation stimulated by low-dose TF and elevated plasma TFPI activity. These changes in coagulation may modulate thrombotic risk and bleeding risk in patients with EOP.
Keywords: Pregnancy; tissue factor; tissue factor pathway inhibitor